THE PRIORITY NEEDS FOR DEVELOPING CARING LEADERSHIP OF SCHOOL ADMINISTRATORS UNDER TACHALOM SCHOOL CONSORTIUM IN SAMUTSAKORN PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Dabsomdej, Thitipa; Charoenkul , Nantarat (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed to: 1) study the current and deriable conditions of caring leadership of School Administrators under Tachalom School Consortium In Samutsakorn Primary Educational Service Area Office; 2) investigating the priority needs for developing caring leadership of School Administrators Under Tachalom School Consortium in Samutsakorn Primary Educational Service Area Office. The study employed a survey research methodology. The population included 8 school directors, 8 deputy directors, and 24 teacher representatives who served as department heads, grade-level leaders, and heads of learning areas, totally 40, selected through purposive sampling. Data were collected using a questionnaire with a reliability coefficient of 0.989. Statistical methods used in the analysis included percentage, mean, standard deviation, and modified priority needs index (PNImodified). The research findings revealed that, overall, the current level of caring leadership among school administrators was moderate, while the desired level was high. The highest need was awareness of one’s own potential in caring for teachers, personnel, and stakeholders such as parents and students (PNImodified = 0.868), followed by development of attentiveness among teachers and staff and the creation of supportive contexts for such development (PNImodified = 0.838), deep understanding of teachers and personnel (PNImodified = 0.737), and knowledge of effective strategies for addressing the needs and concerns of educational personnel and enhancing their engagement (PNImodified = 0.723), respectively.